2006
DOI: 10.1002/asi.20401
|View full text |Cite
|
Sign up to set email alerts
|

User search behavior of domain‐specific information retrieval systems: An analysis of the query logs from PsycINFO and ABC‐Clio's Historical Abstracts/America: History and Life

Abstract: The authors report the findings of a study that analyzes and compares the query logs of PsycINFO for psychology and the two history databases of ABC-Clio: Historical Abstracts and America: History and Life to establish the sociological nature of information need, searching, and seeking in history versus psychology. Two problems are addressed: (a) What level of query log analysis-by individual query terms, by co-occurrence of word pairs, or by multiword terms (MWTs)-best serves as data for categorizing the quer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…The blind reader did not look at the search terms to evaluate the quality or appropriateness of the search terms themselves (for a study in our research program that did, cf. Yi et al, 2006). However, from Appendix C, students with a high grade listed considerably more search terms than did students with low-evaluated essays.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The blind reader did not look at the search terms to evaluate the quality or appropriateness of the search terms themselves (for a study in our research program that did, cf. Yi et al, 2006). However, from Appendix C, students with a high grade listed considerably more search terms than did students with low-evaluated essays.…”
Section: Resultsmentioning
confidence: 89%
“…This study forms part of a series of studies that is focused on formulating design concepts for a new IR system specifically designed for undergraduates researching a social science essay Leide, Large, Beheshti, Brooks, & Cole, 2003;Yi, Beheshti, Cole, Leide, & Large, 2006). In the present study, we focus on university undergraduates in a first-year history course who are in Kuhlthau's (1993) Stage 3, the exploration stage of her six-stage essay-writing process.…”
Section: Introductionmentioning
confidence: 99%
“…We also conducted numerous sorting, calculation, and summarization during the analysis process. First, to infer user search behavior and information needs from the queries of a particular system, we examined a number of variables or metrics, such as query length, query terms, number of queries, and browsing requests per user and number of information‐seeking methods used per user (Stenmark, ; Yi et al, ). In this study, we followed Jansen et al's () definition for a query term, which is “any unbroken string of characters (i.e., a series of characters with no space between any of the characters)” (p. 211).…”
Section: Methodsmentioning
confidence: 99%
“…al., 2000; Jansen et al, 2000). It has also been used to investigate the use of single terms, term pairs, and multiword terms in two domain‐specific information retrieval systems (Yi et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we analyzed the search logs of the experiment following several steps: we first extracted user search terms from the search logs, and then categorized terms, calculated term frequencies in each category, and finally analyzed term frequency distribution. Related research in user log analysis used subject guides, categorizing software, or constructed subject taxonomy for term categorization (Yi et al, 2006). However, in this study, a close examination of these queries revealed that the search queries used a limited number of search terms within the botanical domain and it was not necessary to use a complete subject list to categorize these terms.…”
Section: Methodsmentioning
confidence: 99%